Field assessment of balance in 10 to 14 year old children, reproducibility and validity of the Nintendo Wii board. - Larsen, Lisbeth Runge; Jørgensen, Martin Grønbech; Junge, Tina; Juul-Kristensen, Birgit; Wedderkopp, Niels (BMC Pediatrics, 2014)
Background: Because body proportions in childhood are different to those in adulthood, children have a relatively higher centre of mass location. This biomechanical difference and the fact that children's movements have not yet fully matured result in different sway performances in children and adults. When assessing static balance, it is essential to use objective, sensitive tools, and these types of measurement have previously been performed in laboratory settings. However, the emergence of technologies like the Nintendo Wii Board (NWB) might allow balance assessment in field settings. As the NWB has only been validated and tested for reproducibility in adults, the purpose of this study was to examine reproducibility and validity of the NWB in a field setting, in a population of children.Methods: Fifty-four 10-14 year-olds from the CHAMPS-Study DK performed four different balance tests: bilateral stance with eyes open (1), unilateral stance on dominant (2) and non-dominant leg (3) with eyes open, and bilateral stance with eyes closed (4). Three rounds of the four tests were completed with the NWB and with a force platform (AMTI). To assess reproducibility, an intra-day test-retest design was applied with a two-hour break between sessions.Results: Bland-Altman plots supplemented by Minimum Detectable Change (MDC) and concordance correlation coefficient (CCC) demonstrated satisfactory reproducibility for the NWB and the AMTI (MDC: 26.3-28.2%, CCC: 0.76-0.86) using Centre Of Pressure path Length as measurement parameter. Bland-Altman plots demonstrated satisfactory concurrent validity between the NWB and the AMTI, supplemented by satisfactory CCC in all tests (CCC: 0.74-0.87). The ranges of the limits of agreement in the validity study were comparable to the limits of agreement of the reproducibility study.Conclusion: Both NWB and AMTI have satisfactory reproducibility for testing static balance in a population of children. Concurrent validity of NWB compared with AMTI was satisfactory. Furthermore, the results from the concurrent validity study were comparable to the reproducibility results of the NWB and the AMTI. Thus, NWB has the potential to replace the AMTI in field settings in studies including children. Future studies are needed to examine intra-subject variability and to test the predictive validity of NWB.